The Effect Of Interactive Learning Videos On Learning Interests Of Grade Iv Elementary School Students In The Subject Of ScienceENTS IN THE SUBJECT OF SCIENCE - Harmawati; Annisa Ardana; Tia Latifatu (Jurnal Sekolah Dasar, 2026)
The problem in this study stems from the low interest in learning students in Natural and Social Sciences (IPAS) in grade IV of elementary school. This condition results in a lack of attention, motivation, and active involvement of students during the learning process. Therefore, this study aims to determine the effect of using interactive videos on increasing students' interest in learning. This study used a quantitative approach with a pre-experimental one-group pre-test post-test design. Data collection techniques were carried out through the distribution of learning interest questionnaires and documentation of test results. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis included descriptive analysis, normality tests, homogeneity tests, and t-tests to determine significant differences between pre-test and post-test scores. The results showed a significant increase in students' interest in learning after using interactive videos. The average learning interest score increased from the low-medium category to high. Descriptive analysis showed a shift in the frequency distribution, while the t-test proved that the difference was statistically significant. Discussion of the results confirmed that interactive videos were able to attract students' attention, increase motivation, and encourage active involvement during learning. In conclusion, the use of interactive videos has a positive effect on increasing fourth-grade students' interest in science. This study recommends that teachers utilize interactive technology-based learning media more effectively to create an engaging, contextual learning environment that meets the demands of 21st-century education.